Strengthening capacity, incentives and institutions for food safety in Ethiopia: Training of food business inspectors from the Addis Ababa City Administration - Keba, Abdi; Dinede, Getachew; Mekonnen, A.; Abate, Gashaw T.; Hoffmann, Vivian; Grace, Delia; Amenu, Kebede; Hung Nguyen-Viet (International Livestock Research Institute, 2024)
The International Livestock Research Institute (ILRI) is implementing a food safety project, Strengthening Capacity, Incentives and Institutions for Food Safety in Ethiopia (SCIIFS), aimed at improving the capacity of food safety regulators. As part of this project, on 11 October 2023, ILRI organized a workshop for food inspectors from the Addis Ababa City Administration Food and Drug Authority (AAFDA) to train them on food safety, food inspection, foodborne hazards, and elements that support food safety interventions. Twenty-five of the 26 invited participants attended the workshop: two food business inspectors from each of the 11 sub-cities and four from the AAFDA main office.